Sigorta Pazarlaması ve Sağlık Sigortaları - (:unkn) unknown (My University, 2002)
0

Humans exposed to many serious perils such as property losses froın fire and windstorm, and personal losses from disability and death. For (his reason, the thought of taking measures against these dangerous perils that may cause ali kinds of harın to man and society, has created the insurance concept and the Insurance business, The function of Insurance is to safeguard against such misfortunes by having the losses of the unfortunate few paid by contributions of the many who are exposed. insurance and insuring people should be considered as a service. Services have certain characteristics that distinguish them from tangible products and therefore when creating a marketing mix, these special characteristics nıust be kept in mind. As is known, social security is a type of insurance that is iınplemented by th e government as a monopolyfor insuring a part of ör the whole of society against the risks that threaten them. One of the most important types of social security is the health insurance and it is a type that is heavily used in our country. in this study insurance marketing, private health insurance and health insurance in social security is discussed.